Pharmacogenetics, Kinetics, and Dynamics for Personalized Medicine by DF Kisor, MD Kane, JN Talbot and JE Sprague - David A Buckley; Patrick C McHugh (University of Huddersfield Press, 2016)
Pharmacogenomics is the study of genetic differences responsible for the variability in drug response among individual patients. Emerging from this new science is the development of diagnostic tools crucial for improving treatment strategies, as well as reducing drug side effects. As the importance of this science is being realized, the need for this discipline in pharmacy student training is becoming increasingly crucial to their professional development and training as healthcare professionals. As this discipline evolves, there is a clear need for tools that can enable lecturers to deliver this essential training; the current book review investigates aspects that are specific to the needs of the target audience and will explore the potential of 'Pharmacogenetics, Kinetics, and Dynamics for Personalized Medicine' in achieving this task.